A case of chronic pancreatitis in which endoscopic ultrasonography was effective in the diagnosis of a pseudoaneurysm - Fukatsu, Kazuhiro (Baishideng Publishing Group Co., Limited, 2012)
Endoscopic ultrasonography (EUS) was performed on a patient being treated for chronic pancreatitis because a submucosal tumor was observed in the stomach during gastrointestinal endoscopy. As internal pulsatile blood flow on Doppler was present, the diagnosis of an aneurysm was made. The pseudoaneurysm of the left gastric artery was embolized with histoacryl and lipiodol and the splenic artery was embolized with coils at the location of the pseudoaneurysm to prevent hemorrhage. Follow up EUS confirmed the cessation of blood flow from the pseudoaneurysm. Clinicians encountering a gastric submucosal tumor-like protrusion in a patient with chronic pancreatitis should use EUS to investigate the possibility of a pseudoaneurysm, which must be treated as quickly as possible once identified.